Multiplexed volume holographic gratings for simultaneous generation of Airy and Dual Airy beams - Vyas, Sunil; Chia, Yu-Hsin; Luo, Yuan (SPIE, 2018)
Utilizing three unique defining properties of volume holograms, namely, wavelength degeneracy, angular selectivity, and multiplexing capability, here we show the recording and simultaneous reconstruction of the Airy and Dual Airy beam from multiplexed volume holographic gratings (MVHGs). Each grating acts independently and creates its own diffraction pattern corresponding to the shape of the grating. Multicolor reconstruction of MVHGs are shown. Experimental results demonstrate that volume holograms are capable of reproducing optical wavefront with high precision without affecting the structural properties of beams at any optical wavelengths. These MGHGs acts as wavelength-independent mode shaper and can be used to make compact optical systems. The volume hologram based beam shaping technique is simple and cost-effective and has potential for the mass production.